2009
DOI: 10.1128/ec.00207-09
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the Sterol Regulatory Element-Binding Protein Pathway and Its Pathobiological Importance in Cryptococcus neoformans

Abstract: The mammalian sterol regulatory element-binding protein (SREBP) homolog, Sre1, is important for adaptation and growth of Cryptococcus neoformans in the mouse brain, where oxygen concentration and nutritional conditions are suboptimal for fungal growth. The extent of conservation of the SREBP pathway in C. neoformans or in any other fungi, however, has not been investigated. We generated mutants susceptible to low oxygen and identified six genes that play a role in the SREBP pathway. Three of these genes (SFB2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 44 publications
(68 reference statements)
5
71
0
Order By: Relevance
“…Studies have also shown that sre1 and stp1 mutants cause itraconazole to act in a fungicidal manner (56). Recently, six additional genes that play a role in the SREBP pathway in C. neoformans were identified: SFB2, STP1, SCP1, KAP123, GSK3, and DAM1 (97). Interestingly, SFB2, KAP123, and GSK3 were not known to be involved in the SREBP pathway in other fungi, suggesting a divergence of this pathway in C. neoformans.…”
Section: Cellular Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that sre1 and stp1 mutants cause itraconazole to act in a fungicidal manner (56). Recently, six additional genes that play a role in the SREBP pathway in C. neoformans were identified: SFB2, STP1, SCP1, KAP123, GSK3, and DAM1 (97). Interestingly, SFB2, KAP123, and GSK3 were not known to be involved in the SREBP pathway in other fungi, suggesting a divergence of this pathway in C. neoformans.…”
Section: Cellular Stress Responsesmentioning
confidence: 99%
“…Interestingly, SFB2, KAP123, and GSK3 were not known to be involved in the SREBP pathway in other fungi, suggesting a divergence of this pathway in C. neoformans. Furthermore, all novel mutants discovered in that study exhibited hypersensitivity to fluconazole, and all but KAP123 showed defects in mouse virulence models (97).…”
Section: Cellular Stress Responsesmentioning
confidence: 99%
“…In C. neoformans, the Scp1 protein (CNAG_01580) processes the Sre1 transcription factor (CNAG_04804) (29,41). Processed Sre1 is then imported into the nucleus by the Kap123 protein (CNAG_05884) and phosphorylated by the Gsk3 kinase (CNAG_06730) (30). The Dam1 protein regulates the turnover of Sre1, thus regulating the transcriptional response to low oxygen.…”
Section: Hypoxic Stressmentioning
confidence: 99%
“…This motif is broadly conserved across ascomycete fungi, whose members lack homologs of the intramembrane-cleaving Site-2 protease present in mammals. These findings demonstrate a role for this conserved glycineleucine motif in fungal SREBP cleavage activation, provide tools for dissecting the mechanism of SREBP cleavage, and identify the SREBP C terminus as a target for antifungal therapy for pathogenic fungi that contain a relevant conserved SREBP pathway (5,7,9,14,15).…”
mentioning
confidence: 99%